2014
DOI: 10.1002/hipo.22368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucrose and high fructose corn syrup consumption on spatial memory function and hippocampal neuroinflammation in adolescent rats

Abstract: Excessive consumption of added sugars negatively impacts metabolic systems; however, effects on cognitive function are poorly understood. Also unknown is whether negative outcomes associated with consumption of different sugars are exacerbated during critical periods of development (e.g., adolescence). Here we examined the effects of sucrose and high fructose corn syrup-55 (HFCS-55) intake during adolescence or adulthood on cognitive and metabolic outcomes. Adolescent or adult male rats were given 30-day acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
187
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 78 publications
16
187
2
1
Order By: Relevance
“…Consistent with our previous report (43), there was no effect of sugar or monosaccharide ratio on body weight gain when sugar was made available ad libitum throughout the entire juvenile and adolescent period ( Figure 1A), and there were no differences in overall energy intake between the 4 groups ( Figure 1B). Sugar consumption did not differ between groups fed the solutions with different monosaccharide ratios ( Figure 1C).…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our previous report (43), there was no effect of sugar or monosaccharide ratio on body weight gain when sugar was made available ad libitum throughout the entire juvenile and adolescent period ( Figure 1A), and there were no differences in overall energy intake between the 4 groups ( Figure 1B). Sugar consumption did not differ between groups fed the solutions with different monosaccharide ratios ( Figure 1C).…”
Section: Resultssupporting
confidence: 91%
“…Lowette et al [27] showed, that a diet with high content of sugar may lead to adverse effects in human's cognitive function, impaired learning and memory. Similar results have been published by Hsu et al [28].…”
Section: Products Considered As Having Potential Negative Health Effectsupporting
confidence: 92%
“…7B). It had been reported that an elevation of blood glucose level affected on the spatial learning and memory which associated with hippocampus [28,33]. In the step-through passive avoidance test, it has been indicated that not only hippocampus but also another brain regions (e.g.…”
Section: Discussionmentioning
confidence: 99%